Avaliação de práticas de logística reversa para resíduos sólidos no setor hoteleiro: pousadas da praia de Canoa Quebrada - Aracati - Viana, Márcia de Negreiros (2009)
This paper aims to identify the Reverse Logistics for solid residues from hotels and inns. For this purpose, a bibliographical research on Logistics, Reverse Logistics, Environmental and Hotel Management was done. The bibliographical study led to the main premises of the analyzed study, allowing a field research to be applied in seven inns located at the seashore of Canoa Quebrada beach in the Municipal District of Aracati in the State of Ceará. These inns are part of the Business Association of Canoa Quebrada - ASDECQ and they are also registered in the support service for small businesses - SEBRAE-CE during the period of July 2nd to 4th of 2009. This research also presented explorative, descriptive, quantifying and qualifying aspects, and the application of a semi structured questionnaire was done. The results of the research are presented on this paper referring to the current situation of the inns, difficulties which were found and the identification of the use of practices of Reverse Logistics on reducing, reusing and recycling. It is important to mention that many of the inns which were observed are conscience that something needs to be done, at some time. However, there is still a cultural thought that only the government can be the great articulator to make environmental management happen. This way of thinking and the attitudes need to be reviewed, for these inns have a fundamental role in this management, in an improvement process not only on their businesses but also as active representatives on the environmental balance.